2020
DOI: 10.3390/nu12092771
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Three Carbohydrate Metrics of Nutritional Quality for Packaged Foods and Beverages in Australia and Southeast Asia

Abstract: Carbohydrate quality is an aetiological factor of diet-related disease. Indices of carbohydrate quality featuring various ratios of carbohydrates-to-dietary fibre-to-sugar have been associated with improved product and/or diet quality in westernised countries. Carbohydrate intake is especially high in Asia Pacific. Thus, this study evaluated the ability of such carbohydrate metrics to discriminate the nutritional quality of carbohydrate-rich packaged foods and beverages in Australia, Malaysia, Singapore, Thail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Likewise, after the exclusion of discretionary foods from WG estimations in the Australian National Nutrition and Physical Activity Survey, WG intake values decreased by approximately 1–5 g/d, especially among older children and adolescents [ 31 ]. Results from studies investigating how carbohydrate-rich foods meet nutrient profiling system and different ratios between carbohydrate, fiber, and free sugar also endorsed the importance of evaluating the nutrient content of these foods, which comprise a great variety of products [ 50 , 51 ]. We opted not to use a healthiness criterion to exclude grain foods containing WG in our analysis since the amount consumed was already too small, but it would be essential for labeling purposes to help consumers to make the best possible choices (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, after the exclusion of discretionary foods from WG estimations in the Australian National Nutrition and Physical Activity Survey, WG intake values decreased by approximately 1–5 g/d, especially among older children and adolescents [ 31 ]. Results from studies investigating how carbohydrate-rich foods meet nutrient profiling system and different ratios between carbohydrate, fiber, and free sugar also endorsed the importance of evaluating the nutrient content of these foods, which comprise a great variety of products [ 50 , 51 ]. We opted not to use a healthiness criterion to exclude grain foods containing WG in our analysis since the amount consumed was already too small, but it would be essential for labeling purposes to help consumers to make the best possible choices (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In a study assessing carbohydrate-based processed products from Australia and Southeast Asia, foods meeting the 10 : 1, 10 : 1:2, and 10 : 1|1 : 2 ratios were associated with higher levels of protein, fiber, iron, magnesium, zinc, potassium, selenium, and vitamins B1, B3, and B9 as well as lower levels total sugars, free sugars, saturated fat, trans fat and cholesterol, with all three variants identified to be equally effective in identifying nutritious variants of processed foods [25 ▪ ]. The study which focused on beverages also concluded the 10 : 1 ratio to be most pragmatic for identifying healthy beverages due to regulation-motivated formulation of low-sugar beverage variants employing synthetic fibers as bulking agents [25 ▪ ]. The evaluation of carbohydrate-based foods in the USA by Liu et al [19 ▪▪ ] found similarly encouraging results for all variations with the exception of the breakfast cereals category.…”
Section: Carbohydrate Quality Metrics For Products and Dietsmentioning
confidence: 96%
“…Dietary fiber includes non-digestible carbohydrates and lignins that are intact and intrinsic in plants and are not absorbed in the small intestine of humans but may be fermented by bacteria in the colon [ 10 ]. Furthermore, since dietary fiber has been associated with a lower incidence of various diseases, such as T2D [ 7 , 11 ], the American Heart Association suggests an intake of at least 25 g per day [ 12 ], whereas the Nordic Nutrition Recommendations suggests an intake of at least 25–35 g/day [ 13 ]. It is debated whether the intake of sugars contributes to the development of T2D, and it is proposed that an excess calorie intake as a result of an increased sugar intake may be the causal factor [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since numerous evidence indicates that dietary fiber intake should be encouraged, and free sugar intake limited, new metrics of carbohydrate quality have been proposed, expressed as ratios of total carbohydrate and/or starches to dietary fiber content [ 11 ]. For example, based on the carbohydrate-to-fiber ratio in whole wheat, the American Heart Association has developed a ratio and established recommendations to select foods with at least 1 g of fiber per 10 g of total carbohydrate (<10:1 carbohydrate:fiber) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%